The Utility of Early Brain MRI for Patients with Neurofibromatosis Type 1 and Optic Pathway Glioma: A Long-Term Follow-Up in a Tertiary Referral Hospital - Rony, Cohen; Aharoni, Sharon; Halevy, Ayelet (Neuropediatrics, 2022)
Screening studies have shown detection of optic pathway gliomas (OPGs) in 8 to 31% of children with neurofibromatosis type 1 (NF1). Many of those affected show prolonged indolent phases, but others develop vision disturbances even before diagnosis and treatment. We assessed the clinical presentation at diagnosis, location, natural progression, and risk factors for impaired vision of OPG. The clinical database of the NF1 multidisciplinary clinic of Schneider Children's Medical Center of Israel was reviewed for all patients diagnosed and followed with NF1 during 2007 to 2019. OPG was diagnosed by hyperintensity and thickening along the optic pathway on T2-weighted brain magnetic resonance imaging (MRI), with or without contrast enhancement. Of 257 children with NF1 who underwent MRI, 57 (22%) were diagnosed with OPG; 31 (54%) were females. Twenty-five (44%) had familial NF1. Fifteen (26%) who exhibited tumor progression and worsening in ophthalmic examinations required treatment. Post-chiasmatic glioma was a predictive factor for treatment (p < 0.05), whereas MRI done later and female gender were not significant. Four patients who eventually needed therapy had normal ophthalmic examinations at least 1 year prior to their first MRI. For 6 (40%) of the patients treated, vision continued to worsen. Our findings demonstrate that normal ophthalmic examinations do not always exclude OPG in children with NF1. Early brain MRI before age 36 months may detect OPG, lead to better follow-up and early treatment, and help improve vision outcome.
Keywords: optic pathway gliomas; neurofibromatosis type 1; brain MRI